2011
DOI: 10.1021/nl201083t
|View full text |Cite
|
Sign up to set email alerts
|

Is Stress Concentration Relevant for Nanocrystalline Metals?

Abstract: Classical fracture mechanics as well as modern strain gradient plasticity theories assert the existence of stress concentration (or strain gradient) ahead of a notch tip, albeit somewhat relaxed in ductile materials. In this study, we present experimental evidence of extreme stress homogenization in nanocrystalline metals that result in immeasurable amount of stress concentration at a notch tip. We performed in situ uniaxial tension tests of 80 nm thick (50 nm average grain size) freestanding, single edge notc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 34 publications
(51 reference statements)
3
39
0
Order By: Relevance
“…The low toughness was attributed to the large number of defects along grain boundaries and triple junctions. It was further shown that the strength of a nanocyrstalline graphene strip becomes insensitive to pre-existing flaws when its width falls below 17.16 nm, i.e., the strip will always fail at the theoretical strength regardless of the flaw size, a state commonly referred to as flaw tolerance (Gao et al 2003;Gao and Chen 2005;Kumar et al 2009;Keten et al 2010;Kumar et al 2011;Qin and Buehler 2011;Kumar et al 2013;Gu et al 2013); see Fig. 11a-b.…”
Section: Theoretical Strength Of Graphenementioning
confidence: 99%
“…The low toughness was attributed to the large number of defects along grain boundaries and triple junctions. It was further shown that the strength of a nanocyrstalline graphene strip becomes insensitive to pre-existing flaws when its width falls below 17.16 nm, i.e., the strip will always fail at the theoretical strength regardless of the flaw size, a state commonly referred to as flaw tolerance (Gao et al 2003;Gao and Chen 2005;Kumar et al 2009;Keten et al 2010;Kumar et al 2011;Qin and Buehler 2011;Kumar et al 2013;Gu et al 2013); see Fig. 11a-b.…”
Section: Theoretical Strength Of Graphenementioning
confidence: 99%
“…The minimum available FIB current of 10pA is capable of producing a notch approximately 200 nm in width due to resolution limits for a typical FIB. Consequently, for a 100 nm thick beam with an 800 nm span, the notch as fabricated by the FIB would have been about one fourth of the length of the beam, as also observed by Kumar et al [30,31]. To improve this for the 100 nm thick beams, a much sharper notch was produced by a novel method utilizing the fully converged TEM beam to locally sputter material, resulting in a notch radius of approximately 5 nm.…”
Section: Sample Preparationmentioning
confidence: 81%
“…Such multiple location crack nucleation indicates flaw insensitivity, which has been observed in the literature for nano-crystalline films. 29 We also attempted to repeat this experiment at 600°C; however, with very little change in fracture toughness. This is because even though the high temperature and stress increased the grain size and introduced some annealing twins, we did not observe significant differences in dislocation-based toughening.…”
Section: In Situ Tem Fracture Testingmentioning
confidence: 99%